Neuron-immune mechanisms contribute to pain in early stages of arthritis - Nieto, Francisco R.; Clark, Anna K.; Grist, John; Hathway, Gareth J.; Chapman, Victoria; Malcangio, Marzia (BioMed Central, 2016)
Background: Rheumatoid arthritis (RA) patients frequently show weak correlations between the magnitude of pain and inflammation suggesting that mechanisms other than overt peripheral inflammation contribute to pain in RA. We assessed changes in microglial reactivity and spinal excitability and their contribution to pain-like behaviour in the early stages of collagen-induced arthritis (CIA) model. Methods: Mechanically evoked hypersensitivity, spinal nociceptive withdrawal reflexes (NWRs) and hind paw swelling were evaluated in female Lewis rats before and until 13 days following collagen immunization. In the spinal dorsal horn, microgliosis was assayed using immunohistochemistry (Iba-1/p-p38) and cyto(chemo)kine levels in the cerebrospinal fluid (CSF). Intrathecal administration of microglia-targeting drugs A-438079 (P2X7 antagonist) and LHVS (cathepsin S inhibitor) were examined upon hypersensitivity, NWRs, microgliosis andcyto(chemo)kine levels in the early phase of CIA. Results: The early phase of CIA was associated with mechanical allodynia and exaggerated mechanically evoked spinal NWRs, evident before hind paw swelling, and exacerbated with the development of swelling. Concomitant with the development of hypersensitivity was the presence of reactive spinal microgliosis and an increase of IL-1β levels in CSF (just detectable in plasma). Prolonged intrathecal administration of microglial inhibitors attenuated the development of mechanical allodynia, reduced microgliosis and attenuated IL-1β increments. Acute spinal application of either microglial inhibitor significantly diminished the sensitization of the spinal NWRs. Conclusions: Mechanical hypersensitivity in the early phase of CIA is associated with central sensitization that is dependent upon microglial-mediated release of IL-1β in the spinal cord. Blockade of these spinal events may provide pain relief in RA patients.